Microstructure of ZnIn2S4 thin films - Jitari, Vasile (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2011)
ZnIn2S4 films on MgO and CaF2 oriented substrates were prepared by precipitation from aqueous suspensions. The films were annealed in various regimes. Their stoichiometry was confirmed by the diffraction method. The microstructure of the films was studied via optical microscopy.